The Meaning Of Pancasila In The Indonesian Legal System - Tahir, Erdin (Syiar Hukum, 2023)
As the principle of the state, the position of Pancasila as the source of all sources of law has to be manifested in the national legal system, as a legal ideal (rechtside) of the nation and state, which not only as the basis to evaluate and harmonize all laws and regulations in order to not disaccord with the values contained in Pancasila but more than that the values of Pancasila have to be reflected and translated into the legislation itself. In practice in Indonesia, the construing of Pancasila into law regulates almost all lines of the life of the nation and state, ranging from state affairs, political affairs, economic affairs, religious affairs, and legal affairs, to social affairs, all of these affairs must not conflict with Pancasila. Even to solve conflicts at the community scale, Pancasila is used. Considering how vital and important the values of Pancasila are to the life of the nation and state, it is a given that every legislation should include the values contained in each of the precepts of Pancasila. Therefore, institutionally, it is the duty of both the Legislature and Executive to jointly ensure that the values of each precept in Pancasila are included in the law in accordance with the interests of the Indonesian people. Keywords: Construal, Guidelines, Law, Pancasila.